HALAL LIFESTYLE DI INDONESIA (An-Nisbah: Jurnal Ekonomi Syariah, 2019)
The purpose of this study is to describe the phenomenon of halal lifestyles in Indonesia, and to add insight of the Indonesian society about halal lifestyles in order to make it easier for them to choose Islamic lifestyle through halal lifestyle. This research method uses a literature research approach that is sourced from authoritative news and current journals which has high credibility to explain the phenomenon of halal lifestyle in Indonesia accurately. Based on the literature research that has been done it can be concluded that the increase of population and purchasing power of Muslims in the world can strengthen the halal lifestyles trend. The halal lifestyle is seen as a new lifestyle for the Muslim population in the world, especially the Muslim population in Indonesia. Even the concept of halal has been accepted by Muslims and non-Muslims, and gradually begins to become a lifestyle. Because the halal concept was universal which contained elements of benefit for all humans, halal was not only cover the needs of sharia, but is also a sustainability concept through all human activities seen from its lifestyle. The implications of the phenomenon of halal practices in Indonesia today were not only focused on the food sector, but has been spread to other sectors. Like halal tourism in Nusa Tenggara Barat and D.I. Aceh, halal cosmetics are pioneered by Wardah, a Sharia Hospital spearheaded by RSI. Sultan Agung Semarang, halal medicines initiated by herbal companies, halal modes promoted by Muslim hijabers and fashion designers, financial institutions pioneered by Bank Muamalat Indonesia, and so on. The halal lifestyles trend in Indonesia can also be seen from many animos of the media that preach about “halal lifestyles” such as halallifestyle.com, republika.co.id, ekonom.kompas.com, marketeers.com, mysalaam.com, and many seminar events that raised “halal lifestyle” theme.